The effectiveness of Applied Behavior Analysis training program for intervention teachers in Vietnam - Van Cong, Tran; Nguyen, Phuong Thi Hoai; Hoang, Hue Thi Thanh (VNU Journal of Science: Education Research; Vol 37 No 4, 2021)
Applied Behaviour Analysis (ABA) is demonstrated as the most efficacious intervention for autism spectrum disorder (ASD) in many pieces of paper (Stahmer, 2011). However, ABA has been neither officially educated in Vietnam nor studied to examine the ability of intervention teachers. In order to enhance the quality of intervention teachers in specialized centers, a basic training program was conducted, including a two-week tutorial and a three-month supervised practicum. One hundred thirty-one intervention teachers in Vietnam participated in this training, which comprised general knowledge, fundamental skills, and on-site practicing. The finding indicated that the knowledge about ABA is limited; there are differences between staff with different specialties. The training has a positive impact on raising awareness of ABA even though it was a short-period program. These findings serve as the foundation for introducing evidence-based methods such as ABA into practice for ASD and other developmental disorders in Vietnam.